Words cut two ways: An overview of the situation of Afghan interpreters at the beginning of the 21st century - Tălpaș, Mihaela (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2016)
This piece of research attempts to highlight the role of interpreters in the period 2001–2015 when international coalition forces were in Afghanistan during and after the war. The scope of this paper is, therefore, to address the risks faced by interpreters working for the coalition in Afghanistan in order to develop possible strategies for interpreters and the users of their services for tackling future similar situations of armed conflict. It should be mentioned that the interpreters themselves were perceived as a danger both by the very same coalition forces and by the local community. Consequently, the “dangerous interpreter” became a danger in itself for local interpreters. Having analysed a corpus of online interviews and articles, specialised journals, reports and literature containing the opinions and experiences of interpreters in Afghanistan and of other parties they interacted with, I shall try both to outline the risks faced by interpreters and indicate the necessity of having interpreters in the field. To this end, I shall outline the image of the interpreter-soldier by drawing attention to the risks faced by military personnel and drawing a parallel with those to which interpreters in Afghanistan are exposed. My aim, on the one hand, is to highlight the human side of the interpreter and, on the other, to create a more comprehensive image of “war interpreters at war”, in order to deal better with the challenges of armed conflict in the field of interpreting, both as an interpreter and as a user of interpreting services.